Аналіз сучасного стану інтелектуально-інноваційної діяльності в Україні - Яковлєв, Анатолій Іванович; Косенко, Олександра Петрівна; Ткачов, М. М. (НТУ "ХПІ", 2015)
В статті проведено детальний аналіз сучасного стану інтелектуально-інноваційної діяльності в промисловості України. Особливу увагу приділено питанням дослідження фінансування інтелектуально-інноваційних технологій, кадрового забезпечення виробничих процесів в інноваційній сфері, результатам інтелектуально-інноваційної діяльності промислових і, зокрема, машинобудівних підприємства. Розроблено пропозиції по покращенню результатів інноваційної діяльності на промислових підприємствах, а також по підвищенню економічної ефективності цієї діяльності.

The paper conducted a detailed analysis of the current state of intellectual and innovation in the industry of Ukraine. Particular attention is paid to research funding intellectually innovative technology staffing of production processes in the sphere of innovations, results of intellectual and industrial innovation, particularly engineering company. Suggestions for improving the results of innovation in the industry, and to improve the economic efficiency of these activities. The analysis of the current state of intellectual and innovation in our country leads to the following conclusions and generalizations. First, financing innovation in our country is poor, its level is much lower than in industrialized countries. Second, human resources innovation, despite its significant reduction in recent years, yet is powerful enough and capable of significant scientific achievement. Thirdly, the results of intellectual innovation in our country is ambiguous: it should be noted as individual success and considerable lag.
Analysis of the current state of intellectual and innovation activity in Ukraine
Keywords: об’єкти інтелектуальної власності; вартісна оцінка; методичні підходи; фінансування інноваційної діяльності; intellectual property; valuation; methodological approaches; advantages and disadvantages